Evangelical worship: an American mosaic - Ross, Melanie C. (Oxford University Press, 2021)
"Almost invariably, media stories with the word evangelical in their headlines are accompanied by a familiar stock photo: a mass of middle-class worshippers with eyes closed, faces tilted upward, and hands raised to the sky. Yet, despite the fact that worship has become symbolic of evangelicalism's identity in the twenty-first century, it remains an understudied locus of academic inquiry. Historians of American evangelicalism tend to define the movement by its political entanglements (the "rise of the religious Right"), and academic trajectories (the formation of the "evangelical mind"), not its ecclesial practices. Theological scholars frequently dismiss evangelical worship as a reiteration of nineteenth-century revivalism or a derivative imitation of secular entertainment (three Christian rock songs and a spiritual TED talk). But by failing to engage this worship seriously, we miss vital insights into a form of Protestantism that exerts widespread influence in the United States and around the world. Evangelical Worship: An American Mosaic models a new way forward. Drawing together insights from American religious history and liturgical studies, and putting both in conversation with ethnographic fieldwork in seven congregations, this book argues that corporate worship is not a peripheral "extra" tacked on to a fully-formed spiritual/political/cultural movement, but rather the crucible through which congregations forge and negotiate the contours of evangelicalism's contested theological identity"--